Do we need a public sector performance management framework? - Abdullah, Nur Anisah (2011)
The purpose of this paper is to discuss whether a performance management framework is necessary for public sector organisations in Malaysia. A three-phase research is being carried out on the practice of performance measurement in Malaysian central government. Preliminary findings were indicative of the need for practitioner guidelines on performance measurement and management. A framework consisting of seven key elements for performance management is proposed with a view towards improvement. The proposed framework (Figure 2) informed by Nur Anisah (2008), explained by seven elements, illustrates performance measurement and management as an iterative process starting with (1) the setting of organisational goals and objectives and identification of key areas for monitoring. This is followed by (2) measurement activities being designed to track performance of key areas and (3) preparation of evidence for performance verification. The availability of this evidence enables (4) a process of performance review and decision-making. This review highlights performance issues managers can strategically use in staff communication to (5) drive improvements, and also help pull together evidence generated from measurement activities for (6) external reporting. Through the demonstration of successes, organisations (7) negotiate for target plans and funding. New target plans, budget plans or policy changes would almost always require some revision to existing set of goals and objectives (1) and so the cycle recommences. There are many exemplar frameworks for performance management. A quick deduction from this observation was that there was no ‘one-size-fits-all’ framework. Framework must be shaped and tailored to the needs of respective users. The needs of users were influenced by localised situational components, of which may include political, economical, social-cultural and technological factors as well as the nature of business they conduct. This gave rise to the question: Do we need a performance management framework for public organisations in Malaysia?